A design for life? Commentary on "Designing living environments with adults with autism". Issue 2 (1st April 2014) - Osgood, Tony
Abstract : Purpose: – The purpose of this commentary is to reflect upon not only the importance of design processes as set out in "Designing living environments with adults with autism" but to call for the benefits of good design to be applied to staff functioning. Design/methodology/approach: – This paper is a commentary on a piece of research. Findings: – As much consideration for the design of approaches to maintain helpful staff behaviour must be provided by those creating services as is given to the physical setting. Originality/value: – The unique approach this paper presents is acknowledged as probably not universally applicable ; what is replicable is bringing creative methods of design to bear in the task of delivering what for so long our rhetoric has called for.